A Date at the Altar - Maxwell, Cathy ([New York] : Avon Books, an imprint of HarperCollins Publishers, 2016)
Searching for a suitable young wife from a good family, the Duke of Baynton instead finds himself drawn to struggling playwright Sarah Pettijohn, an outspoken beauty who, constantly challenging his ducal authority, makes him an offer he cannot refuse if he agrees to back her play.
Keywords: Nobility -- Fiction; Man-woman relationships -- Fiction; Women dramatists -- Fiction; Marriage -- Fiction; Romance fiction